Mathematical Model of Heat-and-Mass Transfer for Steam Humidifier - Golinko, Igor; Drevetskiy, Volodymyr (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
The dynamical model of heat-mass exchange for a steam humidifier with lumped parameters, which can be used for synthesis of control systems by inflowing-exhaust ventilation installations, or industrial complexes of artificial microclimate, is considered. A mathematical description that represents the dynamical properties of a steam humidifier concerning the main channels of regulation and perturbation is presented. The resulting dynamical model of a humidification chamber can be the basis for the synthesis of automatic control systems and simulation of transients. A significant ad-vantage of the obtained mathematical model in the state space is the possibility of synthesis and analysis of a multidimensional control system.